How funny it is when everybody gets going! A case of co-construction of humor in conversation - Priego-Valverde, Beatriz (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Humor is built and co-constructed by the participants in conversation, by means of terms and / or attitudes. The paper shows the effects of humor and its co-construction on the interaction itself and on the relationship of the participants to each other. The qualitative analysis of a short sequence carried out emerges into a theoretical reflection about both the functioning of humor itself and about familiar conversation in general.